GEOMETRIC COMPENSATION TECHNIQUE FOR BREAST CONSERVATIVE TREATMENT: EXPANDING THE INDICATIONS AND COSMETIC EVALUATION - Franca, Flávia C.; Oliveira-Junior, Idam de; Lima, Marco A. de; Vieira, René A. C. (Mastology, 2019)
lávia C. Franca1, Idam de Oliveira-Junior1, Marco A. de Lima1, René A. C. Vieira1